Building a stable cationic molecule/electrode interface for highly efficient and durable CO2 reduction at an industrially relevant current. Issue 1 (24th December 2020) - Su, Jianjun; Zhang, Jun-Jie; Chen, Jiacheng; Song, Yun; Huang, Libei; Zhu, Minghui; Yakobson, Boris I.; Tang, Ben Zhong; Ye, Ruquan
Abstract : Effective electronic induction and a stable interface collectively contribute to industrially relevant CO2 reduction performance in a flow cell. Abstract : Aggregation and leaching are two major obstacles to the synthesis of efficient and durable heterogeneous molecular catalysts. These problems are even more severe for charged molecules, not only resulting in unsatisfactory performance, but also leading to misleading evaluation of charged functionalities. In this work, methylation of cobalt(ii ) tetraamino phthalocyanine (CoTAPc) transforms its electron-donating amino groups into electron-withdrawing quaternary ammonium cations, which favor the formation of *COOH intermediate and the desorption of *CO; this is conducive to a 130% increase of the current density for the CO2 reduction reaction (CO2 RR). However, the catalysts leach severely; consequently, the current density decays rapidly. To resolve this dilemma, we developed an in situ functionalization strategy by first covalently grafting CoTAPc onto carbon nanotubes via a diazo-reaction, followed by a complete methylation reaction. This is conducive to a 700% increase in CO partial current density compared to that of a physically mixed sample at −0.72 V vs. RHE with highly stable currents. In a flow cell, this covalently immobilized structure delivers an industrially relevant current density of 239 mA cm −2, CO selectivity of 95.6% at 590 mV overpotential and very low molecular loading of 0.069 mg cm −2 . This work provides mechanistic insight and a design strategy for charged molecular catalysts for high-performance and stable heterogeneous electrolysis.